Environmental impact on marginal coastal benthic communities within the Jeju Island, South Korea temperate transition zone - Perrois, Garance; Jöst, Anna B.; Lee, Kyeong-Tae; Pons, Leonard M. T.; Yang, Hyun-Sung; Son, Young Baek; Park, Heung-Sik; Kang, Do-Hyung; Kim, Taihun (Frontiers in Marine Science, 2024)
Aim of study Marine climatic transition zones are boundary areas of major climate zones, here the boundary between the subtropical and temperate zones. They present areas containing high abundance of organisms living at the limit of their physiological tolerance. These marginal populations are particularly sensitive to changes in their environment. As such, marine climatic transition zones are excellent natural playgrounds for climate change-related hypothesis testing, especially with respect to marine habitat response to ocean warming. The marginal biogenic habitats around Jeju Island, South Korea, which lies within the temperate transition zone, have gradually changed from macroalgal-dominated to hard coral-dominated habitats. Understanding the specific abiotic environmental factors that influence the distribution of the marginal populations in temperate transition zones (i.e., species at their occurrence limit) is crucial to predicting and managing temperate zone habitat changes caused by climate change. This study aims to identify the specific abiotic environmental factors that contribute to explaining the current spatial distribution of the declining temperate and expanding subtropical foundation species in Jeju waters. Methods Coverage and composition of sessile benthic communities were determined by photo-quadrat analysis at two depths (10 m and 15 m) at three sites along the island’s south, east, and north coasts in May and November 2022. Divergences in community composition between sites were characterized in light of ten quantitative environmental parameters. Results Our results show that sessile foundation communities vary significantly at different sites around the island. While the south is defined by high-latitude hard corals, predominately Alveopora japonica, the east is defined by the temperate canopy-forming macroalga Ecklonia cava, and the north is characterized by coralline algae. Winter sea surface temperature, water transparency, nutrient concentration, and water movement were statistically the most impactful environmental factors determining which foundation species constitute each distinct benthic community. Conclusion This study provides valuable baseline information on the impacts of abiotic environmental factors on marine sessile communities in a temperate transition zone.